Exploring the Native English Teacher’s Professional Competence at the Islamic School of An Namiroh Junior High School Pekanbaru - Putri, Arni Amrida (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the professional competence of Native English Teachers (NETs) in the context of Indonesian junior and senior high schools, with a specific focus on An Namiroh Junior High School in Pekanbaru. Using a qualitative approach, data were collected through in-depth interviews with both experienced and novice NETs. The research identifies key dimensions of professional competence beyond linguistic proficiency, including the use of communicative and student-centred teaching strategies, intercultural awareness, and emotional support for students. The findings highlight that while NETs bring valuable language expertise and innovative pedagogical approaches aligned with Communicative Language Teaching (CLT), they also face challenges such as limited familiarity with the local curriculum and differing educational expectations. Teachers who engage with the local culture and language tend to demonstrate greater adaptability and classroom effectiveness. The study concludes that NETs’ professional competence is shaped not only by their native fluency but also by their intercultural competence, pedagogical adaptability, and willingness to engage in continuous professional development. Recommendations include the provision of structured orientation programs and collaborative opportunities with local educators to enhance NETs’ integration and impact in Indonesian schools.